The urgency of setting up additional zones and its implications for underwater cultural heritage in Indonesia - Putri, Jennifer; Utamie, Nindya; Qulub, Andi; Muna, Inas (Institute Of computer Science (IOCS), 2024)
Indonesia has a maritime strategic position covering more than sixty percent of its territory, making it one of the strongest countries in the maritime sector. However, this position also carries potential threats, so strict maritime regulations are required by the 1982 UN Convention on the Law of the Sea (UNCLOS), which Indonesia ratified through Law No. 17 of 1985. One of these regulations is the concept of an additional zone extending up to 24 nautical miles from the baseline, where coastal countries can enforce laws related to customs, immigration, sanitation, and fiscal matters. Even though it is mandated in Article 8 Paragraph 3 of Law No. 32 of 2014 concerning Maritime Affairs, Indonesia still needs to formalize its authority in this zone, giving rise to legal uncertainty, especially regarding protecting underwater cultural heritage (UCH). Given Indonesia's rich maritime history and significant underwater cultural assets, such as shipwrecks, the lack of clear regulations puts these assets at risk of unauthorized salvage and loss. This research emphasizes the need for special legislation regarding Indonesia's additional zones to protect its maritime heritage, ensure legal certainty, and improve maritime governance. This study seeks to highlight legal gaps and propose a firm regulatory framework to protect underwater cultural heritage in Indonesia's additional zones using normative legal research methods, including case studies and analysis of primary and secondary data sources